(untitled) (Research, Society and Development, 2025)
Bipolar Disorder (BD) is a psychiatric condition marked by intense mood fluctuations, alternating between episodes of elevated mood (mania or hypomania) and depressive states, interspersed with periods of clinical stability. These shifts are frequently accompanied by cognitive, physical, and behavioral changes that impair individual functioning. The present study reports a clinical case of a psychotic episode in a patient with a prior diagnosis of BD, which occurred after alcohol intake in conjunction with ongoing desvenlafaxine use. The aim is to explore the potential interaction between this antidepressant and alcohol, considering the triggering factors of the psychotic episode, its psychosocial consequences, and the most appropriate therapeutic strategies. The patient was informed about the research objectives, expressed understanding, and signed the Informed Consent Form (ICF). This case report seeks to broaden the understanding of adverse effects arising from drug interactions in psychiatric patients, highlighting clinical aspects that may increase vulnerability to psychotic episodes.